PENGARUH TERAPI BACK MASSAGE TERHADAP NYERI PUNGGUNG PADA LANSIA DI PUSKESMAS BATU AJI BATAM - Fitriany Suangga; Nia Ramadina (LPPM Universitas Awal Bros, 2021)
Back pain is a disease that is often experienced by the elderly where degeneration in the body of the elderly begins to occour which results in a decrease in bodily functions in the elderly such a bone loss. Back pain is found 64% in developed countries, namely at the age of the elderly who have an age range of more than 60 years, where as in Indonesia alone the elderly who experience high back pain counts and has increased every year. As for this study aims to determine the effect of back massage therapy on pain backs in the elderly. The design of the study was quantitative research with quasi-experimental methods with pre and post without control. The sample of this study was purposive sampling. The sample of this study consisted of 20 elderly in the working area of Batu Aji public health center in Batam. This research was conducted from the 24th of july to thr 3rd of august 2019. The data where analyzed using paired t-test. The results obtained were the most elderly with back pain sufferers with the age range of 75-90 years is as many as 14 elderly (70%), it is known that most of the female sex is 16 elderly (80%) and elderly who works as many as 12 elderly (60%). Most of the elderly experience moderate back pain before back massage therapy was done, namely (75%) as many as 15 elderly people and known the results of the analysis showed that most of the elderly after being given back massage therapy, pain decreased to mild pain by 10 elderly (50%). Consuclusion from the analysis of the these data can be found that the p-value is 0,000 (p=<0.05), showing that there is an effect of back massage therapy on back pain in the elderly.